Prevalence of intermittent claudication in rural and urban Vellore, Tamil Nadu, India: a population-based study - Krishna, Manjunath; M. Oommen, Anu; Paul G., Jackwin Sam; Abraham, Vinod J.; George, Kuryan (International Surgery Journal, 2018)
Background: Population based estimates from India on the prevalence of Peripheral Artery Disease (PAD) are scarce. This study aimed to assess the population-based prevalence of PAD in rural and urban Vellore, Tamil Nadu, South India. Methods: A cross sectional survey was conducted using the WHO STEPS methodology and the WHO/Rose questionnaire for intermittent claudication for identifying symptomatic PAD among adults aged 30-64 years. The study was done in nine villages of one rural block and in 48 urban wards of Vellore, between 2011-12. Risk factors for PAD such as sociodemographic factors, tobacco use, anthropometry, known medical conditions, Fasting Plasma Glucose and lipid profile were also assessed and association with PAD estimated using odds ratios, chi-square tests and logistic regression. Results: Among 5429 adults aged 30-64 years, the prevalence of PAD (intermittent claudication) was 4.9/1000 (95% Confidence Interval CI: 3.0/1000 - 6.8/1000). The prevalence in urban Vellore was higher than in the rural area (6.9/1000 vs. 3.8/1000). After adjusting for sociodemographic factors and other confounding factors, current tobacco use was found to be significantly associated with the presence of PAD (adjusted Odds Ratio: 2.89, 95% CI: 1.10-7.54). Conclusions: This study provides estimates of the burden of PAD in rural and urban adults in Vellore, Tamil Nadu. The trend of this condition needs to be monitored in various locations to assess the public health significance and the need for population level measures for diagnosis, treatment and screening. Education regarding harmful effects of tobacco use should also involve education regarding risk of PAD.